PRODUTIVIDADE E SANIDADE DE BATATA-SEMENTE IMPORTADA DA ESCÓCIA - Mallozzi, P.; Teixeira, P. R. M.; Coelho, Sônia M. B. M.; Ramos, R. S.; Maia, J. B. G.; Rodrigues Neto, J.; Dias, J. A. C. Souza; Miranda Filho, H. S. (REVISTA DE AGRICULTURA, 2015)
PRODUTIVIDADE E SANIDADE DE BATATA-SEMENTE IMPORTADA DA ESCÓCIA